Kombinasi Calcitriol dan Ethynil Ethyl Estradiol Meningkatkan Ekskresi Kalsium Urin dan Risiko Urolitiasis pada Tikus Ovariektomi - Hartiningsih, Hartiningsih; Puspitasari, Ayu Dewi; Putri, Nurdysa Diliana; Arifah, Nurul; Pawestri, Wari; Anggraeni, Devita (Jurnal Veteriner; Vol 18 No 2 (2017), 2017)
The high excretion of calcium (Ca) in the urine can trigger the formation of urolith. Estrogen and calcitriol decrease urinary Ca excretion. This study aims to examine the combination of calcitriol and ethinyl ethyl estradiol against Ca urinary excretion and urolithiasis risk of ovariectomized rats. Twentyfive female Wistar rats eight weeks old were divided into five groups: i) normal control (NK); ii) ovariectomized control (OVK); iii) ovariectomized + calcitriol (OVD); iv) ovariectomized + ethinyl ethyl estradiol (OVE); and v) ovariectomized + combination calcitriol and ethinyl ethyl estradiol (OVDE). Seven weeks post-ovariectomy, each rat was put in an individual metabolic cage for the study of Ca balance. At day 4 to 7 of the study, residual feed, urine, and feces were collected daily for Ca analysis. At day 8, the rats were euthanized, the left kidney were collected for histopathological examination. The results showed that combination of calcitriol and ethinyl ethyl estradiol in OVDE rats caused Ca intake and Ca intestinal absorption significantly higher, and urinary Ca excretion tended to be higher although not significantly different compared to OVK rats. Calcium excretion in OVK rat urine was higher compared to the NK rats. The kidney histopathological changes of OVK rats were not different from the NK rats. Histopathological examination of the OVDE group kidney showed protein deposition in the capsular of Bowman’s capsule and proximal tubules, atrophy of the proximal tubules, and necrosis, respectively. It is concluded that the combination of calcitriol with ethinyl ethyl estradiol in ovariectomized rats increased urinary Ca excretion and increased the risk of urolithiasis. ABSTRAK Tingginya ekskresi kalsium (Ca) dalam urin dapat menjadi pemicu terbentuknya urolit. Estrogen dan calcitriol menurunkan ekskresi Ca urin. Penelitian ini dilakukan bertujuan untuk mengkaji kombinasi calcitriol dan ethynil ethyl estradiol terhadap ekskresi Ca dalam urin dan risiko urolitiasis tikus ovariektomi. Sebanyak 25 tikus Wistar betina umur delapan minggu, dibagi menjadi lima kelompok (kontrol normal NK, kontrol ovariektomi OVK, ovariektomi + calcitriol OVD, ovariektomi + ethynil ethyl estradiol OVE, dan ovariektomi + kombinasi calcitriol dan ethynil ethyl estradiol OVDE). Tujuh minggu pascaovariektomi, setiap tikus dimasukan kandang metabolik individu untuk studi keseimbangan Ca. Pada hari ke-4 sampai 7 studi keseimbangan Ca, setiap hari sisa pakan, urin, dan feses dikumpulkan untuk analisis Ca. Pada hari ke-8 studi keseimbangan Ca, tikus dieutanasi, ginjal kiri diambil untuk pemeriksaan histopatologi. Hasil analisis menunjukkan bahwa kombinasi calcitriol dan ethynil ethyl estradiol pada tikus OVDE menyebabkan konsumsi Ca dan absorpsi Ca intestinal nyata lebih tinggi, dan ekskresi Ca dalam urin cenderung lebih tinggi meskipun tidak berbeda nyata dibanding tikus OVK. Ekskresi Ca dalam urin tikus OVK lebih tinggi dibanding tikus NK. Gambaran histopatologi ginjal OVK terlihat tidak berbeda dengan tikus NK. Histopatologi ginjal OVDE terlihat endapan protein dalam ruang kapsuler kapsula Bowman’s dan tubulus proksimalis, tubulus proksimalis atropi, dan nekrosis. Dari hasil penelitian disimpulkan bahwa kombinasi calcitriol dengan ethynil ethyl estradiol pada tikus ovariektomi meningkatkan ekskresi Ca urin dan meningkatkan risiko urolitiasis.